PENINGKATAN HASIL BELAJAR MATEMATIKA MELALUI TEORI APOS PADA SISWA KELAS VIIC MTs HUSNUL KHATIMAH - Fatimah Fatimah; Yolinika Tampani; Muh Izabi Alis Pindi (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2021)
This research is a classroom action research (CAR) which aims to find out the improvement of mathematics learning outcomes through the theory of apos learning in class VIIc students of MTs Husnul Khatimah. The subjects of this study were the students of class VIIc MTs husnul khatimah, totaling 21 students. This research was conducted in two cycles. The work procedure of each research cycle takes four stages, namely (1) planning, (2) implementing actions, (3) observation, (4)reflection. Data collection is done by providing test results of learning and observation trough observation sheets. Data collected were analyzed by quantitative and qualitative analysis. The results of the study concluded that mathematics learning outcomes have increased trough the theory of apos learning class VIIc students MTs Husnul Khatimah. This is shown by : (1) the increase in the average score of students mathematics learning outcomes is 76,35 in cycle 1 to 86,06 in cycle II; (2) the increase in the percentage of students who complete learning is 71,42% in cycle 1 to 95,23% in cycle 2: and (3) the increase in student activities that are in accordance with learning from cycle 1 to cycle 2 while student activities that are not in line with learning are decreasing.